Description of a new species of Acrostichus Rahm 1928 (Nematoda: Diplogastridae) from India with a note on its position and relationship with the congeners - Tahseen, Qudsia (Biodivers Data J, 2016)
Abstract. BACKGROUND: The clade Diplogastridae Micoletzky 1922 largely represents the bacterivorous or predatory nematodes that very often demonstrate phoretic, necromenic or parasitic associations with insects (Sudhaus and Fürst von Lieven 2003). That is the reason, much of the diversity of the family remains undocumented because of their absence from routine soil samples. Due to their variable habitats and niches, these nematodes show ample variation in their stomal armature, feeding behavior and life cycle patterns. NEW INFORMATION: The paper describes and illustrates a new diplogastrid species of genus Acrostichus Rahm 1928 that appears to be the link between the genera Diplogastrellus Paramonov et al. 1952a and Acrostichus. Acrostichus medius n. sp. is characterised by hermaphroditic females and males having faintly striated longitudinal ridges, demarcated lateral fields, amalgamated lips, six adradial cheilostomal plates, moderately-built dorsal tooth, relatively smaller posterior genital branch; large oval uterine pouch and males with robust, heavily cuticularised spicules, each with hood-like capitulum, deeply forked distal end with fine extensions and a ventral attenuated arm; gubernaculum 2/3 of spicule length and rudiments of bursa confined to posterior four pairs of genital papillae. The biogeographical distribution of Acrostichus has been mapped and the relationship between congeners has been analysed cladistically and discussed.